A kind of anti-loss gold-based catalyst and its preparation method and application
By using the method of modified nitrogen -doped carbon nano -tube carrier and sircinoma coupling agent additives in the golden base catalyst, the problem of the loss of golden base catalysts in acetylene hydrogen chlorine reactions has been solved. The high stability and reaction performance of the catalyst reduces production costs.
Patent Information
- Application Number
- CN202211567353.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-07
AI Technical Summary
Existing gold-based catalysts face the problem of gold species loss in acetylene hydrochlorination reaction, resulting in a decrease in catalyst stability and shortening service life, which increases production costs.
Adopt modified nitrogen doped carbon nanotubes as a carrier, load gold front -drive, and add salt and sibidane coupling agent as additives. The deposition and stability prevent the reunion and restoration of the gold species.
Effectively avoid the loss of gold species, improve the stability of the catalyst and the reaction performance of hydrogen chloride, reduce production costs, and have good industrial application prospects.
Smart Images

Figure CN116174032B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to an anti-loss gold-based catalyst and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the world's top five engineering plastics (PVC, PE, PP, PS, ABS). It is mainly produced industrially through the polymerization reaction of vinyl chloride (VCM) monomer. The product has excellent mechanical properties, tensile strength, dielectric, flame retardant and chemical resistance, accounting for more than 16% of the total demand for plastics. There are two methods for producing VCM monomer in industry: (1) direct addition reaction of acetylene and hydrogen chloride to produce VCM (acetylene hydrochlorination method); (2) direct chlorination, oxychlorination and cracking of ethylene dichloride to produce VCM (equilibrium oxychlorination method). my country's energy structure of rich coal and poor oil determines that most of the domestic VCM production comes from acetylene hydrochlorination reaction. At present, this industrial process uses mercury-based catalysts, which are volatile and highly toxic, and seriously threaten the ecological environment and people's health. At present, the acetylene hydrochlorination process is facing the constraints and restrictions of the increasingly depleted mercury resources and international environmental protection policies such as the "Minamata Convention on Mercury". There is an urgent need to develop new, efficient and environmentally friendly catalysts to replace traditional mercury-based catalysts.
[0003] The research and development of mercury-free catalysts for acetylene hydrochlorination mainly includes two types: supported metal catalysts and metal-free catalysts. Among them, gold-based catalysts show higher VCM activity and selectivity than other series of catalysts, and have great potential for industrial application. It is worth pointing out that similar to the problem of mercury loss in the reaction process of traditional HgCl2 catalysts, gold-based catalysts also face the problem of gold loss in the reaction process; in addition, compared with HgCl2 catalysts, Au-based catalysts require higher operating temperatures in practical applications to achieve the same acetylene conversion rate. The higher hot spot temperature in the reactor also exacerbates the loss of active components of gold-based catalysts, accelerates the deactivation of the catalyst under reaction conditions, and increases the use cost of gold-based catalysts. Therefore, the development of anti-loss gold-based catalysts is of great significance for improving the performance of acetylene hydrochlorination catalytic reactions and reducing production costs.
[0004] Chinese patent CN202111363914.0 discloses an ionic liquid-modified gold-copper acetylene hydrochlorination catalyst and a preparation method thereof, using copper salt and ionic liquid as catalyst additives. The addition of copper salt and ionic liquid significantly inhibits the reduction of high-valent gold species, reduces the loss of gold species, and improves the stability and catalytic activity of the catalyst.
[0005] Chinese patent CN202111416151.1 discloses an acetylene hydrochlorination gold-based catalyst and a preparation method thereof. The addition of P element and sulfur ligand in the obtained catalyst significantly inhibits the reduction of high-valent gold species, reduces the loss of gold species, and improves the stability and catalytic activity of the catalyst.
[0006] The master's thesis (Study on Bismuth Catalyst Supported on Oxidative Pretreatment of Activated Carbon Support and Its Acetylene Hydrochlorination Performance, Wang Jiaojiao) took activated carbon-supported non-precious metal bismuth catalyst as the research object of mercury-free catalyst, investigated the effects of oxidative pretreatment of activated carbon support and metal additives on the catalytic performance of bismuth catalyst supported on activated carbon support after treatment, and explored the effects of oxidative pretreatment of activated carbon with reagents such as HNO3, H2SO4, H2O2 and KMnO4 on the catalytic performance of bismuth catalyst for acetylene hydrochlorination. The results showed that the activity of the catalysts pretreated with different oxidizing reagents was improved, and the order was H2O2>HNO3≈H2SO4>KMnO4. The content of oxygen-containing functional groups on the surface of activated carbon increased after pretreatment with KMnO4, H2SO4 and HNO3, but the specific surface area of activated carbon decreased to varying degrees, affecting the activity of the catalyst.
[0007] Chinese patent CN202110930950.4 discloses a method for preparing a catalyst for preparing vinyl chloride by hydrochlorination of acetylene, which uses activated carbon as a carrier, prepares a solution of the main active component and / or the co-catalyst and impregnates it on the activated carbon, and the impregnated activated carbon is placed in a rotary kiln, and current is passed through the impregnated activated carbon to make the activated carbon heat up to complete the drying process of catalyst preparation. The active components of the obtained catalyst are not easy to lose, the catalyst activity is higher than that of the traditional drying method, and the service life is longer.
[0008] Therefore, although the current Au-based catalysts have high activity and selectivity, they face the problem of gold species loss during the reaction, which reduces the stability and service life of the catalyst. There is an urgent need to develop an anti-loss gold-based catalyst to improve catalyst stability and reduce production costs. Summary of the invention
[0009] The present invention aims at the problems existing in the prior art and provides a gold-based catalyst with resistance to loss, and a preparation method and application thereof. The innovation of the present method lies in using modified nitrogen-doped carbon nanotubes to load active components, and adding cerium salts and silane coupling agents as auxiliary agents. On the one hand, the nitrogen-doped carbon nanotubes treated with concentrated nitric acid can utilize their confinement effect and structural defects, which are beneficial to the deposition and stability of gold species; on the other hand, the addition of cerium auxiliary agents can prevent the agglomeration of gold species and promote the redox cycle of gold active sites during the reaction process; thirdly, the silane coupling agent can modify the surface of the carrier, and the grafted group can optimize the adsorption strength of acetylene and maintain the ionic state of the gold species. The catalyst of the present invention can effectively prevent the gold species from being reduced and agglomerated, thereby limiting the loss of gold species, showing excellent acetylene hydrochlorination reaction performance, and has good industrial application prospects.
[0010] In the first aspect of the present invention, the present invention provides an anti-loss gold-based catalyst, including a carrier, an active component and an auxiliary agent; the carrier is a modified nitrogen-doped carbon nanotube; the active component includes a gold precursor, and the auxiliary agent is a cerium salt and a silane coupling agent.
[0011] The diameter of the modified nitrogen-doped carbon nanotubes is 5-20 nm, and the specific surface area is 200-800 m 2 / g.
[0012] Among them, in the anti-loss gold-based catalyst, the weight of gold accounts for 0.06-0.5% of the weight of the catalyst, and the weight of cerium accounts for 0.05-0.6% of the weight of the catalyst.
[0013] Wherein, the gold precursor is one of chloroauric acid, sodium gold thiosulfate, gold acetate, triphenylphosphine gold chloride, and sodium gold thiocyanate.
[0014] Wherein, the cerium salt is one or more of cerium trichloride, ammonium cerium nitrate, cerium trifluoromethanesulfonate, and cerium nitrate.
[0015] Wherein, the silane coupling agent is one of hexamethyldisilazane, hexamethyldisiloxane, (3-aminopropyl)triethoxysilane and chlorotriethoxysilane.
[0016] The modified nitrogen-doped carbon nanotubes are nitrogen-doped carbon nanotubes obtained by oxidation modification, preferably nitrogen-doped carbon nanotubes obtained by oxidation modification with concentrated nitric acid.
[0017] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned anti-loss gold-based catalyst, comprising the following steps:
[0018] (1) placing a Fe / γ-Al2O3 catalyst in a quartz boat of a horizontal tube furnace, heating it to a high temperature of 500-700°C under an inert atmosphere, switching to a hydrogen atmosphere for several hours to fully reduce the catalyst, then switching the atmosphere to a mixed gas of organic hydrocarbons, ammonia and hydrogen, keeping the temperature constant, switching the gas to an inert gas after several hours and cooling to room temperature, soaking in sodium hydroxide, ultrasonicating and washing to neutrality, soaking in hydrochloric acid, ultrasonicating and washing to neutrality, and drying to obtain nitrogen-doped carbon nanotubes;
[0019] (2) heating the nitrogen-doped carbon nanotubes obtained in step (1) in a water bath at 70-90° C. with concentrated nitric acid for 2-4 h, then washing with deionized water until neutral, filtering and drying to obtain modified nitrogen-doped carbon nanotubes;
[0020] (3) preparing a solution of a gold precursor, loading the Au component onto the modified nitrogen-doped carbon nanotubes by an impregnation method or a deposition precipitation method, and obtaining a solid A after drying; preparing a solution of a cerium salt, impregnating the solid A, aging and drying the solid A, and obtaining a solid B;
[0021] (4) Solid B is loaded into a reactor, heated to 120-200° C. under an inert atmosphere, a silane coupling agent is bubbled in and maintained for 0.5-2 h, and then the inert atmosphere is purged for 0.5-3 h to obtain a loss-resistant gold-based catalyst.
[0022] Preferably, the organic hydrocarbon in step (1) is one or more of methane, ethane, ethylene, acetylene, and propane; and the volume flow ratio of the organic hydrocarbon, ammonia, and hydrogen is (2-8):1:(1-2).
[0023] Preferably, the temperature of the impregnation process in step (3) is 20-35°C, the drying temperature is 100-120°C, and the drying time is 12 hours; the precipitant used in the sedimentation precipitation method is one of sodium hydroxide, sodium carbonate or urea, the temperature is 45-90°C, and the aging time is 3-10 hours.
[0024] Preferably, the mass ratio of the silane coupling agent bubbled in step (4) to the solid B is (0.3-3):1.
[0025] In the third aspect of the present invention, there is provided the use of the above catalyst in the reaction of preparing vinyl chloride by hydrochlorination of acetylene.
[0026] Application conditions: temperature T = 120-180 ° C, normal pressure, GHSV (C2H2) = 30-250h -1 , n(HCl): n(C2H2)=1.03-1.15.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The nitrogen-doped carbon nanotubes modified by concentrated nitric acid oxidation are used as carriers to load active components, and their confinement effect and defects can be utilized to facilitate the deposition and stabilization of gold species; the auxiliary agent cerium can modify the structure and electronic properties of gold species, prevent the aggregation of gold species, and promote the redox cycle of Au sites under reaction conditions, inhibiting the reduction of oxidized gold species to zero-valent gold; the silane coupling agent can modify the surface of the catalyst, and the grafted groups can optimize the adsorption strength of the reactants and prevent the aggregation and loss of gold species. The catalyst of the present invention can effectively avoid the reduction and aggregation of Au species, thereby limiting the loss of Au species and showing excellent acetylene hydrochlorination reaction performance.
[0029] (2) The active components of the catalyst provided by the present invention have a strong interaction with the carrier, and exhibit excellent anti-loss and stability under the reaction conditions of acetylene hydrochlorination to produce vinyl chloride, which can reduce production costs and has good industrial application prospects.
[0030] (3) The catalyst provided by the present invention has a simple preparation process, is pollution-free, has high catalytic activity and stability, and is a green and efficient mercury-free catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The X-ray diffraction pattern of the catalyst prepared in Example 1.
[0032] Figure 2 This is the infrared spectrum of the catalyst prepared in Example 1.
[0033] Figure 3 This is a transmission electron microscopy image of the catalyst prepared in Example 1.
[0034] Figure 4 This is the nitrogen physical adsorption-desorption isotherm diagram of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0035] It is worth noting that the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0036] The following is a more specific case description of catalysts:
[0037] Basic Example: Fe / γ-Al2O3 Catalyst Preparation Steps
[0038] The saturated water absorption rate of γ-Al2O3 was determined, FeCl3 was weighed and dissolved according to the loading amount, and γ-Al2O3 was impregnated with an equal volume, and further aged, dried and calcined to obtain a Fe / γ-Al2O3 catalyst.
[0039] Example 1
[0040] 5g of Fe / γ-Al2O3 (Fe loading 8%) catalyst was placed in a quartz boat of a horizontal tube furnace, heated to 600℃ at 5℃ / min under argon atmosphere, and switched to hydrogen atmosphere for 4 hours to fully reduce the catalyst; the atmosphere was switched to a mixed gas of ethane, ammonia and hydrogen, with a gas flow ratio of 4:1:1, and the temperature was kept constant. After 8 hours, the gas was switched to an inert gas and cooled to room temperature, and then soaked in 10%wt sodium hydroxide solution, ultrasonicated and washed to neutral, soaked in 10%wt hydrochloric acid solution, ultrasonicated and washed to neutral, and dried at 110℃ for 12h to obtain nitrogen-doped carbon nanotubes. Weigh 30g of the above nitrogen-doped carbon nanotubes, heat and reflux with 65% concentrated nitric acid in a water bath at 80℃ for 5h, then washed with deionized water to neutral, filtered and dried to obtain oxidatively modified nitrogen-doped carbon nanotubes;
[0041] Weigh 25 g of the above-mentioned oxidatively modified nitrogen-doped carbon nanotubes, prepare a sodium gold thiosulfate solution with a concentration of 0.005 g / mL, add it dropwise to the modified nitrogen-doped carbon nanotubes with continuous stirring, age for 8 hours, and then place it in an oven at 110°C and dry it for 12 hours to obtain solid A; prepare a cerium nitrate solution with a concentration of 0.02 g / mL, impregnate solid A, age it, and dry it at 110°C for 12 hours to obtain solid B;
[0042] 10g of solid B was placed in a vertical furnace, heated to 140°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, 6g of hexamethyldisiloxane (25°C) was introduced by nitrogen bubbling, and then nitrogen was introduced for 1h to obtain a catalyst. The gold loading was 0.196% and the cerium loading was 0.265%, and its acetylene hydrochlorination performance was evaluated.
[0043] Example 2
[0044] Weigh 25 g of the modified nitrogen-doped carbon nanotube carrier in Example 1 and place it in a beaker, add 500 mL of water and stir, add 12 mL of 0.01 g / mL chloroauric acid solution and 0.82 g of urea, heat to 80° C. in a water bath and age for 8 h, centrifuge the suspension, wash, and dry at 110° C. for 12 h to obtain solid A; prepare a 0.01 g / mL cerium nitrate solution to impregnate solid A, age, and dry at 110° C. for 12 h to obtain solid B;
[0045] 10g of solid B was placed in a vertical furnace, heated to 130°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, and 6g of hexamethyldisilazane (25°C) was introduced by nitrogen bubbling. After purging for 1h, a catalyst was obtained. The gold loading was 0.135% and the cerium loading was 0.211%. Its acetylene hydrochlorination performance was evaluated.
[0046] Example 3
[0047] Weigh 25 g of the modified nitrogen-doped carbon nanotube carrier in Example 1 and place it in a beaker, add 500 mL of water and stir, add 22 mL of 0.02 g / mL chloroauric acid solution and stir for 30 min, add 0.005 g / mL sodium carbonate solution dropwise, adjust the pH of the solution to 5-6 and stir for 30 min, heat to 70° C. in a water bath for aging for 8 h, centrifuge the suspension, wash, and dry at 110° C. for 12 h to obtain solid A; prepare 0.01 g / mL cerium nitrate solution to impregnate solid A, age, and dry at 110° C. for 12 h to obtain solid B;
[0048] 10g of solid B was placed in a vertical furnace, heated to 130°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, and 6g of (3-aminopropyl)triethoxysilane (25°C) was introduced by nitrogen bubbling. After purging for 1h, a catalyst was obtained. The gold loading was 0.446% and the cerium loading was 0.310%. Its acetylene hydrochlorination performance was evaluated.
[0049] Example 4
[0050] 5g of Fe / γ-Al2O3 (Fe loading 12%) catalyst was placed in a quartz boat of a horizontal tube furnace, heated to 700℃ at 8℃ / min under argon atmosphere, and switched to hydrogen atmosphere for 4 hours to fully reduce the catalyst; the atmosphere was switched to a mixed gas of acetylene, ammonia and hydrogen, with a gas flow ratio of 6:2:1, and the temperature was kept constant. After 8 hours, the gas was switched to argon and cooled to room temperature, soaked in 10%wt sodium hydroxide solution, ultrasonicated and washed to neutral, soaked in 10%wt hydrochloric acid solution, ultrasonicated and washed to neutral, and dried at 110℃ for 12h to obtain nitrogen-doped carbon nanotubes. 30g of the above nitrogen-doped carbon nanotubes were weighed and refluxed with 65% concentrated nitric acid in a 70℃ water bath for 4h, then washed with deionized water to neutral, filtered and dried to obtain modified nitrogen-doped carbon nanotubes;
[0051] Weigh 25 g of the modified nitrogen-doped carbon nanotubes, prepare 0.003 g / mL triphenylphosphine gold chloride aqueous solution, add dropwise to the modified nitrogen-doped carbon nanotubes and stir continuously to perform equal volume impregnation, and dry at 110° C. for 12 h to obtain solid A; prepare 0.006 g / mL cerium trichloride aqueous solution, impregnate solid A, age and dry at 110° C. for 12 h to obtain solid B;
[0052] 10g of solid B was placed in a vertical furnace and heated to 150°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, 6g of chlorotriethoxysilane (25°C) was introduced by nitrogen bubbling, and then purged with nitrogen for 1h to obtain a catalyst. The gold loading was 0.092% and the cerium loading was 0.147%, and its acetylene hydrochlorination performance was evaluated.
[0053] Comparative Example 1
[0054] The solid B in Example 1 was used as the catalyst of Comparative Example 1, wherein the loading amount of gold was 0.196% and the loading amount of cerium was 0.265%, and its acetylene hydrochlorination performance was evaluated.
[0055] Comparative Example 2
[0056] 10 g of solid A in Example 1 was placed in a vertical furnace, heated to 140° C. in a nitrogen atmosphere with a volume flow rate of 50 mL / min, 6 g of hexamethyldisiloxane (25° C.) was introduced by nitrogen bubbling, and then purged with nitrogen for 1 hour to obtain a catalyst. The gold loading was 0.196%, and its acetylene hydrochlorination performance was evaluated.
[0057] Comparative Example 3
[0058] Weigh 25g of coconut shell activated carbon, prepare an aqueous solution of sodium gold thiosulfate with a concentration of 0.005g / mL, add it dropwise to the coconut shell activated carbon and stir continuously, age it for 8h, and then place it in an oven at 110°C and dry it for 12h to obtain solid A; prepare an aqueous solution of cerium nitrate with a concentration of 0.02g / mL, impregnate solid A, age it, and dry it at 110°C for 12h to obtain solid B;
[0059] 10g of solid B was placed in a vertical furnace, heated to 140°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, 6g of hexamethyldisiloxane (25°C) was introduced by nitrogen bubbling, and then purged with nitrogen for 1h to obtain a catalyst. The gold loading was 0.224% and the cerium loading was 0.275%, and its acetylene hydrochlorination performance was evaluated.
[0060] Comparative Example 4
[0061] 10 g of solid B in Example 1 was weighed and placed in a vertical furnace, and the temperature was raised to 140° C. in a nitrogen atmosphere with a volume flow rate of 50 mL / min, and 6 g of bis[3(triethoxysilyl)propyl]tetrasulfide (25° C.) was introduced by nitrogen bubbling, and then purged with nitrogen for 1 hour to obtain a catalyst. The gold loading was 0.196%, and the cerium loading was 0.445%, and its acetylene hydrochlorination reaction performance was evaluated.
[0062] Comparative Example 5
[0063] 5 g of Fe / γ-Al2O3 (Fe loading 8%) catalyst was placed in a quartz boat of a horizontal tube furnace, heated to 600°C at 5°C / min under an argon atmosphere, and switched to a hydrogen atmosphere for 4 hours to fully reduce the catalyst; the atmosphere was switched to a mixed gas of ethane and hydrogen with a gas flow ratio of 4:1, and the temperature was kept unchanged. After 8 hours, the gas was switched to an inert gas and cooled to room temperature, soaked in a 10%wt sodium hydroxide solution, ultrasonically washed to neutral, soaked in a 10%wt hydrochloric acid solution, ultrasonically washed to neutral, and dried at 110°C for 12 hours to obtain carbon nanotubes.
[0064] Weigh 30 g of the carbon nanotubes, heat and reflux them in a water bath at 80° C. with 65% concentrated nitric acid for 5 h, then wash them with deionized water until they are neutral, and filter and dry them to obtain oxidatively modified carbon nanotubes;
[0065] Weigh 25 g of the above-mentioned oxidatively modified carbon nanotubes, prepare a sodium gold thiosulfate solution with a concentration of 0.005 g / mL, add it dropwise to the oxidatively modified carbon nanotubes while stirring continuously, age for 8 hours, and then place it in an oven at 110°C and dry it for 12 hours to obtain solid A; prepare a cerium nitrate solution with a concentration of 0.02 g / mL, impregnate solid A, age it, and dry it at 110°C for 12 hours to obtain solid B;
[0066] 10 g of solid B was weighed and loaded into a vertical furnace, and the temperature was raised to 140° C. in a nitrogen atmosphere with a volume flow rate of 50 mL / min, 6 g of hexamethyldisiloxane (25° C.) was introduced by nitrogen bubbling, and then nitrogen was purged for 1 hour to obtain a catalyst. The gold loading was 0.195% and the cerium loading was 0.268%, and its acetylene hydrochlorination reaction performance was evaluated.
[0067] Comparative Example 6
[0068] Weigh 25 g of the unoxidized nitrogen-doped carbon nanotubes in Example 1, prepare a sodium gold thiosulfate solution with a concentration of 0.005 g / mL, add dropwise to the nitrogen-doped carbon nanotubes with continuous stirring, age for 8 h, and then place in an oven at 110° C. and dry for 12 h to obtain solid A; prepare a cerium nitrate solution with a concentration of 0.02 g / mL, impregnate solid A, age, and dry at 110° C. for 12 h to obtain solid B;
[0069] 10 g of the solid B was weighed and placed in a vertical furnace, heated to 140° C. in a nitrogen atmosphere with a volume flow rate of 50 mL / min, 6 g of hexamethyldisiloxane (25° C.) was introduced by nitrogen bubbling, and then purged with nitrogen for 1 hour to obtain a catalyst. The gold loading was 0.196% and the cerium loading was 0.264%, and its acetylene hydrochlorination performance was evaluated.
[0070] Comparative Example 7
[0071] Weigh 25 g of the carbon nanotubes in Comparative Example 5, prepare a sodium gold thiosulfate solution with a concentration of 0.005 g / mL, add it dropwise to the carbon nanotubes while stirring continuously, age for 8 hours, and then place it in an oven at 110° C. and dry it for 12 hours to obtain solid A; prepare a cerium nitrate solution with a concentration of 0.02 g / mL, impregnate solid A, age it, and dry it at 110° C. for 12 hours to obtain solid B;
[0072] 10 g of the solid B was weighed and placed in a vertical furnace, heated to 140° C. in a nitrogen atmosphere with a volume flow rate of 50 mL / min, 6 g of hexamethyldisiloxane (25° C.) was introduced by nitrogen bubbling, and then purged with nitrogen for 1 hour to obtain a catalyst. The gold loading was 0.195% and the cerium loading was 0.265%, and its acetylene hydrochlorination performance was evaluated.
[0073] Comparative Example 8
[0074] 5g of Fe / γ-Al2O3 (Fe loading 8%) catalyst was placed in a quartz boat of a horizontal tube furnace, heated to 600℃ at 5℃ / min under argon atmosphere, and switched to hydrogen atmosphere for 4 hours to fully reduce the catalyst; the atmosphere was switched to a mixed gas of ethane, ammonia and hydrogen, with a gas flow ratio of 4:4:1, and the temperature was kept constant. After 8 hours, the gas was switched to an inert gas and cooled to room temperature, soaked in 10%wt sodium hydroxide solution, ultrasonicated and washed to neutral, soaked in 10%wt hydrochloric acid solution, ultrasonicated and washed to neutral, and dried at 110℃ for 12h to obtain nitrogen-doped carbon nanotubes. Weigh 30g of the above nitrogen-doped carbon nanotubes, heat and reflux with 65% concentrated nitric acid in a water bath at 80℃ for 5h, then washed with deionized water to neutral, filtered and dried to obtain oxidatively modified nitrogen-doped carbon nanotubes;
[0075] Weigh 25 g of the above-mentioned oxidatively modified nitrogen-doped carbon nanotubes, prepare a sodium gold thiosulfate solution with a concentration of 0.005 g / mL, add it dropwise to the modified nitrogen-doped carbon nanotubes with continuous stirring, age for 8 hours, and then place it in an oven at 110°C and dry it for 12 hours to obtain solid A; prepare a cerium nitrate solution with a concentration of 0.02 g / mL, impregnate solid A, age it, and dry it at 110°C for 12 hours to obtain solid B;
[0076] 10g of solid B was placed in a vertical furnace, heated to 140°C in a nitrogen atmosphere with a volume flow rate of 50mL / min, 6g of hexamethyldisiloxane (25°C) was introduced by nitrogen bubbling, and then purged with nitrogen for 1h to obtain a catalyst. The gold loading was 0.201% and the cerium loading was 0.815%, and its acetylene hydrochlorination performance was evaluated.
[0077] The catalysts of Examples 1-4 and Comparative Examples 1-8 were evaluated for acetylene hydrochlorination performance in multiple parallel fixed bed reactors at a temperature of 170°C and a space velocity of 130 h -1 , raw gas C2H2:HCl=1:1.1, the reaction device was operated for more than 1500 hours, during which the conversion rate and selectivity at the reactor outlet were recorded. The catalytic performance of Examples 1-4 and Comparative Examples 1-8 and the Au content before and after the reaction are summarized in Table 1.
[0078] Table 1 Catalyst performance and Au content before and after reaction of examples and comparative examples
[0079]
[0080] By comparing Examples 1-4 and Comparative Examples 1-8, the following conclusions can be drawn:
[0081] Comparison between Examples 1-4 and Comparative Example 1 shows that when the modification is performed without the auxiliary silane coupling agent, the catalyst activity decreases significantly after 1500 hours of reaction, the catalyst deactivates quickly, and the gold loss is serious;
[0082] Comparison between Examples 1-4 and Comparative Example 2 shows that when the auxiliary component cerium is missing, the catalyst activity decreases significantly after 1500 hours of reaction, the catalyst deactivates quickly, and gold is lost seriously;
[0083] Comparison between Examples 1-4 and Comparative Example 3 shows that when coconut shell activated carbon is used as a carrier to load active components and additives, the initial activity of the acetylene hydrochlorination reaction is relatively high, but the catalyst activity decreases significantly after 1500 hours of reaction, and gold loss is serious;
[0084] Comparison between Examples 1-4 and Comparative Example 4 shows that when other silane coupling agents are used to modify the catalyst, the initial activity of the acetylene hydrochlorination reaction is relatively low, the performance of the catalyst is also low after 1500 hours of reaction, and the loss of gold is relatively high;
[0085] Comparison between Example 1 and Comparative Examples 5-7 shows that no nitrogen doping or oxidation modification treatment will reduce the performance of the catalyst, indicating that nitrogen doping and oxidation modification treatment are beneficial to the reaction performance;
[0086] A comparison between Examples 1-4 and Comparative Example 8 shows that when the raw material gas ratio in the preparation process of nitrogen-doped carbon nanotubes is changed and the amount of the auxiliary cerium is increased too much, the initial activity of the acetylene hydrochlorination reaction is relatively low, and the performance of the catalyst is still low after 1500 hours of reaction. Although the loss of gold species is not much, the reaction performance is poor.
[0087] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A gold-based catalyst that resists loss, characterized in that: The anti-loss gold-based catalyst is composed of a carrier, an active component and an additive, wherein the carrier is a modified nitrogen-doped carbon nanotube; The method for preparing the anti-loss gold-based catalyst comprises the following steps: (1) placing a Fe / γ-Al2O3 catalyst in a quartz boat of a horizontal tube furnace, heating it to a high temperature of 500-700°C under an inert atmosphere, switching to a hydrogen atmosphere for several hours to fully reduce the catalyst, then switching the atmosphere to a mixed gas of organic hydrocarbons, ammonia and hydrogen, keeping the temperature constant, switching the gas to an inert gas after several hours and cooling to room temperature, soaking in sodium hydroxide, ultrasonicating and washing to neutrality, soaking in hydrochloric acid, ultrasonicating and washing to neutrality, and drying to obtain nitrogen-doped carbon nanotubes; (2) heating the nitrogen-doped carbon nanotubes obtained in step (1) in a water bath at 70-90° C. with concentrated nitric acid for 2-4 h, then washing with deionized water until neutral, filtering and drying to obtain modified nitrogen-doped carbon nanotubes; (3) preparing a solution of a gold precursor, loading the Au component onto the modified nitrogen-doped carbon nanotubes by an impregnation method or a deposition precipitation method, and obtaining a solid A after drying; preparing a solution of a cerium salt, impregnating the solid A, aging and drying the solid A, and obtaining a solid B; (4) Solid B is charged into a reactor and heated to 120-200° C., a silane coupling agent is bubbled in and maintained for 0.5-2 h, and then purged for 0.5-3 h to obtain an anti-loss gold-based catalyst; The cerium salt is one or more of cerium trichloride, ammonium cerium nitrate, cerium trifluoromethanesulfonate, and cerium nitrate; the silane coupling agent is one of hexamethyldisilazane, hexamethyldisiloxane, (3-aminopropyl)triethoxysilane, and chlorotriethoxysilane.
2. The anti-loss gold-based catalyst according to claim 1, characterized in that: The modified nitrogen-doped carbon nanotubes are oxidized and modified with concentrated nitric acid, and have a diameter of 5-20 nm and a specific surface area of 200-800 m 2 / g.
3. The anti-loss gold-based catalyst according to claim 1, characterized in that: In the leaching-resistant gold-based catalyst, the weight of gold accounts for 0.06-0.5% of the weight of the catalyst, and the weight of cerium accounts for 0.05-0.6% of the weight of the catalyst.
4. The anti-loss gold-based catalyst according to claim 1, characterized in that: The gold precursor is one of chloroauric acid, sodium gold thiosulfate, gold acetate, triphenylphosphine gold chloride, and sodium gold thiocyanate.
5. The anti-loss gold-based catalyst according to claim 1, characterized in that: The organic hydrocarbon in step (1) is one or more of methane, ethane, ethylene, acetylene, and propane; the volume flow ratio of the organic hydrocarbon, ammonia, and hydrogen is (2-8):1:(1-2).
6. The anti-loss gold-based catalyst according to claim 1, characterized in that: The temperature of the immersion process in step (3) is 20-35°C, the drying temperature is 100-120°C, and the drying time is 12 hours; the precipitant used in the sedimentation precipitation method is one of sodium hydroxide, sodium carbonate or urea, the temperature is 45-90°C, and the aging time is 3-10 hours.
7. Use of the anti-loss gold-based catalyst according to any one of claims 1 to 6 in acetylene hydrochlorination reaction.
Citation Information
Patent Citations
Preparation method of catalyst for preparing vinyl chloride through acetylene hydrochlorination
CN113648986A
Ionic liquid modified gold-copper acetylene hydrochlorination catalyst and preparation method thereof
CN114029069A
Acetylene hydrochloride gold-based catalyst and preparation method thereof
CN114146730A
Composite metal salt catalyst for hydrochlorination reaction of acetylene
CN102631942A
Nitrogen doped carbon material loaded catalyst
CN103381369A